Healthcare providers' insights on pediatric care quality in Gaza hospitals: integrating evidence-based practices and illness management, health information systems, and referral efficiency - Eleyyan, Saeed Y.; ELssyed Etewa, Bothyna B.; Al’Haj Ahmad, Fatma; El Bilbeisi, Abdel Hamid (Frontiers in Pediatrics, 2025)
BackgroundThe quality of pediatric care in Gaza hospitals is a critical concern, especially given the region's limited resources and ongoing political instability. This study aimed to assess healthcare providers' perspectives on the quality of pediatric care in Gaza's major hospitals, focusing on the integration of evidence-based practices (EBPs) and illness management, health information systems (HIS), and referral efficiency.MethodsA cross-sectional study was conducted in 2023 at three major pediatric hospitals in the Gaza Strip: Al-Nasr Pediatric Hospital, EL-Dorra Pediatric Hospital, and Al-Rantisi Specialized Pediatric Hospital. A structured interview-based questionnaire was used to collect data from the healthcare providers. Three domains of the World Health Organization (WHO) integrated tool, “Standards for Improving the Quality of Care for Children in Health Facilities” was employed to assess pediatric care quality. Statistical analysis was performed using SPSS version 26.ResultsThe study's participants (336 healthcare providers) were predominantly male (59.5%), with an average age of 36.2 ± 8.73 years. Most were nurses (71%), but only a small fraction (0.6%) were pediatric nurses. A significant portion (64.6%) held a bachelor's degree, and a majority (83.3%) had not pursued specialized studies in pediatric care. However, more than half (58.3%) had attended pediatric care training courses, and 23.2% had less than five years of experience. Findings revealed that the integration of EBPs was inconsistent, with only 66.7% of participants reporting proper triage and assessment of emergency cases. Illness management, particularly in areas like malnutrition and anemia, showed significant gaps, with less than 60% adherence to standard practices. The HIS was underdeveloped, with 69.4% of providers reporting accurate medical records, and only 63.7% indicated proper use of data for quality improvement. Referral efficiency was also compromised, with only 65.2% of providers reporting timely referrals.ConclusionWhile some progress has been made in pediatric care quality in Gaza, significant gaps remain in evidence-based practice, illness management, HIS functionality, and referral efficiency. Addressing these challenges requires improved infrastructure, resource allocation, and enhanced training for healthcare providers.